Edifícios de luxo no centro de Santiago do Chile: uma escolha residencial atrativa? - Line Henry (Confins)
Santiago’s area is constantly increasing due to the appeal of detached suburban houses. However, there are in the high-income part of the capital, next to Las Condes’ central business district, an important number of high prestigious residential buildings. Our study aimed at identifying their residents’ profile and motivations - in other words, the criteria of their residential choice, so as to rule on the possible appearance of a real alternative to diffuse housing in detached homes. We noted a research by this affluent population of a “decentralized centrality” provided by the poly-centrality of Chile’s capital, and set, in the frame of our study, around the business district of Apoquindo avenue. This phenomenon, added up to the historical and financial importance of the Eastern district, allow its residents to enjoy a high degree of socio-economical segregation, of security, of prestige and of proximity of high grade services, stores, facilities, jobs and transports. Thus, in this context of valuation of a form of centrality, we noted the existence of a population flow, not only from the center to the suburbs but also, and on the scale of individuals’ life, from the suburbs to the center. This new distribution, even though much lower, implies for one to pass from the single-family detached house to a high-rise flat apartment, from very low density to high urban density. It moreover leads to a growth of the latter, and suggests the emergence for the Chilean upper class of a somehow positive view of apartment blocks. The simultaneous reality of these opposed residential migrations, which depend on the stage of one’s family life, and the generalized possession of secondary residences “on the beach or in the countryside” prevent us from concluding that a real ideal of apartment appeared, or that a new deep desire for density, which would be shared by the upper class of Santiago, rose. Nevertheless, it seems relevant to study in the forthcoming years the evolution of the residential preferences of an emergent young professionals’ generation, currently single or in couple without children. They indeed display an attraction for centrality and don’t currently contemplate the single-family detached house as a desirable alternative. Furthermore, we noted that the strong, innovatory and influential Chilean real estate sector might be able to foster the positive evolution of the image of the apartment, and even to create high-rises, whose quality and facilities would attract part of the suburban individual houses’ ardent supporters.